Pengaruh Media Tanam dan Varietas Terhadap Pertumbuhan dan Hasil Tanaman Jahe (Zingiber officinale R) - siti hafsah; Mariana Mariana; Rita Hayati (Jurnal Agrotek Lestari, 2023)
The purpose of this research is to find out how the growth and yield of ginger are affected by the growing media and varieties, and how they interact with each other. This research was conducted at the Gayo Lues Laboratory and PSDKU at the University of Syiah Kuala Gayo Lues. The design used in this study was a 4 x 2 Factorial Randomized Block Design with 3 replications, so there were 8 treatment combinations and 24 experimental units with a total of 72 plants. Plant height, number of tillers per clump, main stem diameter, fresh chestnut weight, tuber weight, tuber diameter, and dry chestnut weight were the parameters observed. The results of this study indicated that the media and variety treatment had a very significant effect on plant height at 120 HSPT. Stem diameter and fresh chestnut weight were significantly affected by the varietal treatment, as well as plant height and tuber weight, but not by other parameters. In ginger growth and yield, there was no significant interaction between growing media and varieties. The treatment of citronella waste and coffee peel waste planting media with red ginger varieties produced the best plant growth.